LANDASAN PENDIDIKAN ISLAM DI INDONESIA - Dede Misbahul Alam; Syamsul Falah; Rendra Seftian Hadiwiharja (STKIP Subang, 2026)
Islamic education is an integral part of Indonesia’s national education system and plays an important role in shaping individuals who are faithful, pious, and possess noble character. This study aims to examine the foundations of Islamic education in Indonesia from theological and juridical perspectives, as well as to understand the objectives and functions of Islamic education within the framework of building a just and progressive nation. The method employed is library research, analyzing primary sources such as the Qur’an, Hadith, statutory regulations, and relevant scholarly literature. The findings indicate that Islamic education in Indonesia has strong legitimacy, both normatively theologically and constitutionally juridically. Islamic education is directed toward forming the insan kamil (the complete human being) who is able to fulfill the role of a devout individual with noble character and to serve as a strategic partner of the state in educating the life of the nation.